Valorisation of hop co-products for their phenolic content and antioxidant properties. - Calvert, Duncan (2025)
There is growing interest in the valorisation of agricultural and food processing residues for their functional bioactive compounds, due to high availability, low cost and alignment with a circular economy model. The harvesting and processing of hop cones for the brewing industry generates co-products which contain phenolic compounds of potential value to the cosmetic, food and beverage sectors due to their antioxidant properties. This study aimed to evaluate these co-products as a source of natural phenolics by producing extracts with high antioxidant activity using scalable, green extraction and purification techniques. Purified hop phenolic fractions were benchmarked against commercially available phenolic antioxidants produced from non-hop sources. In experiments reported in Chapter 3 the focus was on optimising the extraction of phenolics from hop processing residue (cv. Herkules) using aqueous ethanolic solutions. A response surface methodology was adopted to evaluate the effects of; ethanol % of extraction solvent (30-90%), and solid: liquid ratio (100-150 mg/ml). Ethanol % was highly significant (P<0.0001) for the extraction of total phenolic content (TPC), proanthocyanidin content (PAC), xanthohumol, total alpha acids and Ferric Reducing Antioxidant Power (FRAP), whilst solid: liquid ratio did not significantly (P>0.05) impact on any of those response variables. A range of commercial enzymes (cellulases, pectinases and proteases) and incubation conditions were evaluated to see if they could increase the release of bound phenolics, however no treatments resulted in significantly greater extraction (p>0.05). It was concluded that optimal extraction conditions for the simultaneous extraction of TPC, PAC and xanthohumol were 50% ethanol (v/v) at 100mg/ml with no hydrolytic enzymes. These extraction conditions were then applied to a range of hop co-products and non-hop materials (Chapter 4) to characterise their phenolic composition and antioxidant activity. Hop co-product extracts generally had higher phenolics content and antioxidant activities compared to non-hop materials. Phenolic structural elucidation and quantitation using LC-ESI-qTOF-MS/MS showed that prevalent hop co-product phenolic fractions include flavanols, B-type procyanidins, flavonol glycosides, prenylflavonols and chlorogenic acids. The phenolic profile of co-products depended on the co-product stream and hop variety, with prenylflavonols being abundant in CO2 extract residues, catechins and procyanidins in T45 pelleting residues, and flavonol glycosides and chlorogenic acids in hop leaves. Notably, Herkules CO2 extract residue was found to be a rich source of prenylflavonoids, in particular xanthohumol (9.1 mg/g DM), a prenylflavonoid with potent hydroxyl and peroxyl scavenging activities and anti-cancer properties. Herkules CO2 extract residue is also the most available material to industry and was therefore selected for subsequent attempts to generate purified, more concentrated hop phenolic extracts. In Chapter 5 the use of different adsorption resins (PVPP and PAD950) and ultrafiltration membranes (UFX10, FS40, GR51) were investigated for the purification of phenolics from Herkules CO2 extract residue. The phenolic purity and antioxidant activity of purified extracts from CO2R-HERK strongly depended on the purification technique used. The highest purity extract was produced via adsorption with PAD950 resin, and was mainly composed of catechins, B-type procyanidins and flavonol 3-O-glycosides. Ultrafiltration was much less effective across a range of membrane cut-off sizes evaluated (10-100 kDa) indicating that PAD950 SPE offers greater phenolic specificity as compared to molecular weight size exclusion techniques. Langmuir isotherm modelling demonstrated high adsorption capacities of PVPP for hop phenolics (in particular xanthohumol), for both E0 and E50 feed solutions. However, recovery rates using ethanol, ethyl acetate and ammoniacal ethanol of varying strengths were generally ineffective for phenolic recovery using a fixed bed column setup. Later work (Chapter 6, 7) comprehensively evaluated hop leaves as a source of phenolic antioxidants by sourcing three commercially significant varieties grown in Yakima, sampled at different developmental stages and crop years. The phenolic profile of hop leaves exhibited considerable structural diversity and differed significantly from that of respective cones. Kaempferol and quercetin 3-O-glycosides as well as chlorogenic acids were the most abundant sub-groups, with phenolic acids, procyanidins, prenylflavonoids and bitter resins also present. Multi-variate analysis indicated that the phenolic profile of hop leaves was primarily variety-dependent and driven largely by the composition of flavonol glycosides, with crop year and developmental stage showing smaller and less consistent effects. Compared to South African hop leaf extracts, Yakima hop leaf extracts exhibited significantly lower total phenolic contents but higher flavonol glycoside levels, highlighting the variability in phenolic content among hop leaf sources. In Chapter 8 the antioxidant activities of hop leaf extracts were evaluated and correlated with phenolic compound concentrations in the samples. Pearson’s correlation analysis revealed significant positive correlations for B-type procyanidins and catechins (P<0.05), whilst kaempferol 3-O-glycosides generally had negative correlations. Antioxidant analysis of pure chemical standards generally confirmed these findings and highlighted that leaf flavonol glycosides had significantly lower antioxidant activity compared to their respective aglycones, with kaempferol 3-O-glycosides exhibiting negligible DPPH and FRAP activity. Since kaempferol 3-O-glycosides were generally the most abundant phenolics in hop leaf extracts, enzyme assisted hydrolysis was evaluated to improve the antioxidant properties of hop leaf extracts. Snailase treatment of leaf extracts achieved high hydrolysis rates (>99%) and significant increases in antioxidant activity depending on glycoside composition and antioxidant mechanism assayed. Cascade leaf extract exhibited the greatest increases in antioxidant activity (FRAP 4.5*) likely due to the high kaempferol 3-O-rutinoside content (400.56 mg/g). These findings highlight the potential for hydrolytic treatment of hop leaf extracts to generate natural antioxidants.